Retargeting from the CR3 to the LFA-1 receptor uncovers the adenylyl cyclase enzyme-translocating segment of Bordetella adenylate cyclase toxin - Masin, Jiri; Osickova, Adriana; Jurnecka, David; Klimova, Nela; Khaliq, Humaira; Sebo, Peter; Osicka, Radim (The Journal of biological chemistry, 2020)
The Bordetella adenylate cyclase toxin-hemolysin (CyaA) and the α-hemolysin (HlyA) of Escherichia coli belong to the family of cytolytic pore-forming Repeats in ToXin (RTX) cytotoxins. HlyA preferentially binds the αLβ2 integrin LFA-1 (CD11a/CD18) of leukocytes and can promiscuously bind and also permeabilize many other cells. CyaA bears an N-terminal adenylyl cyclase (AC) domain linked to a pore-forming RTX cytolysin (Hly) moiety, binds the complement receptor 3 (CR3, αMβ2, CD11b/CD18, or Mac-1) of myeloid phagocytes, penetrates their plasma membrane, and delivers the AC enzyme into the cytosol. We constructed a set of CyaA/HlyA chimeras and show that the CyaC-acylated segment and the CR3-binding RTX domain of CyaA can be functionally replaced by the HlyC-acylated segment and the much shorter RTX domain of HlyA. Instead of binding CR3, a CyaA1-710/HlyA411-1024 chimera bound the LFA-1 receptor and effectively delivered AC into Jurkat T cells. At high chimera concentrations (25 nm), the interaction with LFA-1 was not required for CyaA1-710/HlyA411-1024 binding to CHO cells. However, interaction with the LFA-1 receptor strongly enhanced the specific capacity of the bound CyaA1-710/HlyA411-1024 chimera to penetrate cells and deliver the AC enzyme into their cytosol. Hence, interaction of the acylated segment and/or the RTX domain of HlyA with LFA-1 promoted a productive membrane interaction of the chimera. These results help delimit residues 400-710 of CyaA as an "AC translocon" sufficient for translocation of the AC polypeptide across the plasma membrane of target cells.
Keywords: transport proteinů; Escherichia coli (E. coli); THP-1 buňky; lidé; complement receptor 3 (CR3,); Lymphocyte Function-Associated Antigen-1; Mice, Inbred BALB C; fatty acyl; HlyA; Female; fatty acid; Adenylate Cyclase Toxin; THP-1 Cells; AC domain translocation; CHO buňky; protein translocation; myši; Humans; Cricetulus; Bordetella; Jurkat buňky; Mice; cytosol; Protein Transport; RTX toxin; CHO Cells; bacterial toxin; makrofágový antigen 1; Cytosol; acyltransferase; Macrophage-1 Antigen; Bordetella pertussis; protein acylation; AC translocon; myši inbrední BALB C; zvířata; Jurkat Cells; ženské pohlaví; adenylátcyklasový toxin; Animals; CyaA; antigen-1 spojený s lymfocytární funkcí; integrin; acylation